Uncovering Jewish Creativity in Book III of the Sibylline Oracles : Gender, Intertextuality, and Politics - Bacchi, Ashley, (Supplements to the Journal for the Study of Judaism;, 2020)
In Uncovering Jewish Creativity in Book III of the Sibylline oracles, Ashley L. Bacchi reclaims the importance of the Sibyl as a female voice of prophecy and reveals new layers of intertextual references that address political, cultural, and religious dialogue in second-century Ptolemaic Egypt. This investigation stands apart from prior examinations by reorienting the discussion around the desirability of the pseudonym to an issue of gender. It questions the impact of identifying the author's message with a female prophetic figure and challenges the previous identification of paraphrased Greek oracles and their function within the text. Verses previously seen as anomalous are transferred from the role of Greek subterfuge of Jewish identity to offering nuanced support of monotheistic themes.